Mastery, Tyranny, and Desire : Thomas Thistlewood and His Slaves in the Anglo-Jamaican World - Burnard, Trevor G. (Trevor Graeme) (Book collections on Project MUSE., 2004)
"Eighteenth-century Jamaica, Britain's largest and most valuable slave-owning colony, relied on a brutal system of slave management to maintain its tenuous social order. Trevor Burnard provides insight into Jamaica's vibrant but harsh African and European cultures with the first comprehensive examination of the extraordinary diaries of plantation owner Thomas Thistlewood." "In Burnard's hands, Thistlewood's diary reveals a great deal not only about the man and his slaves but also about the structure and enforcement of power, changing understandings of human rights and freedom, and connections among social class, race, and gender, as well as sex and sexuality, in the plantation system."--Jacket